IMPLEMENTATION OF URINE TB LAM EXAMINATION IN HIV PATIENTS IN SAMPANG REGENCY AS AN EFFORT OF EARLY DETECTION AND PREVENTION OF TUBERCULOSIS COMPLICATION - Diah Rini; Yetti Hernaningsih; Puspa Wardhani; Yulia Nadar Indrasari; Yessy Puspitasari; Aditea Aetnawati Putri; Lulut Kusumawati (Jurnal Layanan Masyarakat (Journal of Public Services), 2026)
This community service project aimed to enhance early detection of tuberculosis (TB) among HIV patients through the implementation of urine TB-LAM testing and to strengthen the capacity of laboratory personnel in Sampang Regency. The main problems identified were the low awareness of People Living with HIV/AIDS (PLWHA) regarding the relationship between TB and HIV, and the limited ability of Medical Laboratory Technologists (MLTs) to perform TB-LAM examinations independently. The program consisted of health education sessions for 20 PLWHA about TB prevention and early detection in HIV, as well as theoretical and practical training for 13 MLTs on urine TB-LAM examination. Pre- and post-tests were conducted to evaluate knowledge and skill improvement. Statistical analysis using the Wilcoxon Signed-Rank Test revealed significant improvements in both groups: PLWHA (Z = -3.92; p < 0.001) and MLTs (Z = -4.21; p < 0.001). These results indicate that the community service activity was effective in enhancing participants’ knowledge and skills. The impact of the program includes increased awareness of TB symptoms among PLWHA and improved technical competence of MLTs in performing TB-LAM testing as part of integrated HIV-TB diagnostic services. Therefore, this activity contributes positively to strengthening early TB detection systems among HIV patients and supports the implementation of   simple   diagnostic   technologies   in   regional   health   facilities.